Rates and characteristics of radiographically detected intracerebral cavernous malformations after cranial radiation therapy in pediatric cancer patients - Gastelum, Erica (J Child Neurol, 2014)
Rates and characteristics of intracerebral cavernous malformations (ICMs) after cranial radiation therapy (CRT) remain poorly understood. Herein we report on ICMs detected on follow+up imaging in pediatric cancer patients who received CRT at age ≤ 18 years from 1980 to 2009. Through chart reviews (n=362) and phone interviews (n=104) of a retrospective cohort we identified 10 patients with ICMs. The median latency time for detection of ICMs after CRT was 12 years (range 1+24 years) at a median age of 21.4 years (IQR 15+28). The cumulative incidence was 3% (95% CI 1+8%) at 10 years post CRT and 14% (95% CI 7+26%) at 15 years. Three patients underwent surgical resection. Two surgical specimens were pathologically similar to sporadically occurring ICMs; one was consistent with capillary telangiectasia. ICMs are common after CRT and can show a spectrum of histological features.